ANALISIS DEBT TO EQUITY RATIO (DER), RETURN ON ASSETS (ROA), RETURN ON EQUITY (ROE), NET PROFIT MARGIN (NPM) TERHADAP STOCK PRICE (HARGA SAHAM) PADA PERUSAHAAN SAHAM SYARIAH SEKTOR MAKANAN DAN MINUMAN PERIODE TAHUN 2013-2016 - Choiruddin, Muhammad Nanang (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2017)
This study aims to determine the effect of Debt to Equity Ratio (DER), Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM) to Stock Price (Shares) in Sharia Stock Company Food and Beverage Sector Period Year 2013-2016 partially and simultaneously.From the results of this study can be concluded that simultaneously, the variable Debt to Equity Ratio (DER), Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM) significant effect on stock prices. While the influence of each independent variable by partial dependent variable shows the result that price change is not influenced by Debt to Equity Ratio (DER), then the result of price change is influenced by Return on Assets (ROA), then the result of price change is not influenced by Return on Equity (ROE), then the result of price change is not influenced by Net Profit Margin (NPM).